Association between weight-adjusted waist index and arterial stiffness in hypertensive patients: The China H-type hypertension registry study - Xiong, Yurong; Shi, Weidong; Huang, Xiao; Yu, Chao; Zhou, Wei; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2023)
Objective: Exploring the relationship between (weight-adjusted waist index) WWI and arterial stiffness (AS) in the total and different BMI populations among patients with hypertension. Methods: This study enrolled 5232 hypertensive subjects, a subset of the China H-type Hypertension Registry Study. WWI was calculated as WC (cm) divided by the square root of weight (kg). Brachial-ankle pulse wave velocity (baPWV) was measured to determine AS. Results: The mean WWI was 10.97 (0.78)cm/√kg. In multiple logistic analyses showed that there were significant dose-dependent association between WWI with baPWV in a dose-dependent manner in total population (β 57.98, 95% CI 44.06-71.90), and in different BMI group: group 1 (BMI<18.5kg/m2) (β 94.30, 95% CI 39.36-149.23), group 2 (18.5-23.9kg/m2) (β 74.21, 95% CI 54.57-93.85), group 3 (≥24kg/m2) (β 26.11, 95% CI 5.22-47.01). In stratified analysis, stronger associations between WWI and baPWV were observed in patients with higher BP or lower BMI. Sensitivity analysis by excluding patients treated with lipid-lowering agents did not change the association between WWI and baPWV. Conclusions: For hypertensive patients, we found that WWI was positively associated with baPWV in different BMI groups. WWI might be considered as an intervening factor in preventing and treatment of AS, besides BP management.